2013
DOI: 10.4028/www.scientific.net/amr.740.426
|View full text |Cite
|
Sign up to set email alerts
|

Designing Apparatus for Highly Precise Measurement of Electrical Conductivity and Seebeck Coefficient from 85 K to 1200 K

Abstract: We describe the development of apparatus for measuring of electrical conductivity and Seebeck coefficient with high precision from 85 K to 1,200 K. Electrical resistance was measured by means of four-point probe method as a function of temperature. The temperature below 400 K was measured by using type T thermocouple in vacuum system was used and from 400 to 1,200 was measured by using Type S was applied for temperature between 400 and 1200 Kelvin in an inert gas system. With the dimensions of the specimen, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Iwanaga et al [19] reported a set up which can measure the Seebeck coefficient upto 1000 K but the main complexity lies in the designing of the sample holder and placing the probes in it through drilling. Paul [20] reported a set up for both Seebeck coefficient and electrical resistivity measurement but both the set-up are applicable till 600 K. Budngam et al [21] reported a set-up for measuring very low Seebeck co-efficient for metals for a wide range of temperature (85-1200 K). Gunes et al [22] reported a set up that also features complicated sample probe design with custom made temperature and voltage probes.…”
Section: Introductionmentioning
confidence: 98%
“…Iwanaga et al [19] reported a set up which can measure the Seebeck coefficient upto 1000 K but the main complexity lies in the designing of the sample holder and placing the probes in it through drilling. Paul [20] reported a set up for both Seebeck coefficient and electrical resistivity measurement but both the set-up are applicable till 600 K. Budngam et al [21] reported a set-up for measuring very low Seebeck co-efficient for metals for a wide range of temperature (85-1200 K). Gunes et al [22] reported a set up that also features complicated sample probe design with custom made temperature and voltage probes.…”
Section: Introductionmentioning
confidence: 98%